Analisis Kesulitan Guru dalam Implementasi Pembelajaran Berdiferensiasi pada Pelajaran Matematika di SMA X - Annisa Zakiya (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to analyze the challenges faced by teachers in implementing differentiated learning in Mathematics subjects at SMA X. Differentiated learning is a strategy that adapts the learning process to the needs, interests, and learning profiles of students. The research method used is qualitative research with a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation with the research subject being a Mathematics teacher at SMA X. The results of the study indicate that teachers face various obstacles in implementing differentiated learning, such as limited time for preparation and implementation, difficulties in classroom management, and a lack of appropriate learning resources and media. Efforts made to overcome these obstacles include discussions in teacher working groups (KKG), development of learning media, as well as support from school principals and parents of students. This research is expected to serve as a reference in formulating effective strategies to support teachers in optimally implementing differentiated learning.